Advances in Musculoskeletal Radiology: Diagnostic Techniques and Clinical Applications (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Musculoskeletal radiology is a rapidly evolving field that plays a crucial role in diagnosing and managing a wide range of disorders affecting bones, joints, muscles, and connective tissues. This paper reviews the latest advances in musculoskeletal radiology, emphasizing diagnostic techniques such as magnetic resonance imaging (MRI), computed tomography (CT), and ultrasound (US). We conducted a retrospective analysis of imaging data from 300 patients with various musculoskeletal disorders, evaluating the effectiveness of these imaging modalities in detecting and diagnosing conditions such as fractures, soft tissue injuries, arthritis, and tumors. The results highlight the strengths and limitations of each imaging modality, offering insights into their optimal application in clinical practice. The study concludes with recommendations for a multimodal imaging approach to improve diagnostic accuracy and patient outcomes.